2011
DOI: 10.1007/s00330-011-2152-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and variability of three semi-quantitative methods for assessing right ventricular systolic function from cardiac MRI in patients with acquired heart disease

Abstract: RVFAC appears to be more accurate and reproducible than RVFS and TAPSE for SQt assessment of RV function by cardiac MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…The RV postprocessing takes approximately 13 AE 4 minutes for precise quantification of RVEF, and RVFAC is a feasible, fast, accurate, and reproducible method for evaluating RV function. 18 In our study, RVFAC 35% had 98% positive predictive value, consistent with the 95% value at 30% threshold recently reported. 12 Although RVEF quantification with CMR avoids most geometric assumptions, its diagnostic value (based on AUC) was not statistically better than that of RVFAC in our study, possibly because difficulties in delineating the endocardial boarder of the RV base-to-apex contiguous slices might lead to RVEF measurement errors in some cases.…”
Section: Indices Of Rv Function Rv Dilation and Septum Bulgingsupporting
confidence: 93%
See 2 more Smart Citations
“…The RV postprocessing takes approximately 13 AE 4 minutes for precise quantification of RVEF, and RVFAC is a feasible, fast, accurate, and reproducible method for evaluating RV function. 18 In our study, RVFAC 35% had 98% positive predictive value, consistent with the 95% value at 30% threshold recently reported. 12 Although RVEF quantification with CMR avoids most geometric assumptions, its diagnostic value (based on AUC) was not statistically better than that of RVFAC in our study, possibly because difficulties in delineating the endocardial boarder of the RV base-to-apex contiguous slices might lead to RVEF measurement errors in some cases.…”
Section: Indices Of Rv Function Rv Dilation and Septum Bulgingsupporting
confidence: 93%
“…12 Although RVEF quantification with CMR avoids most geometric assumptions, its diagnostic value (based on AUC) was not statistically better than that of RVFAC in our study, possibly because difficulties in delineating the endocardial boarder of the RV base-to-apex contiguous slices might lead to RVEF measurement errors in some cases. 18 In previous studies, RVEF did not perform better than RVFAC to diagnose PH, and RVEF was not more strongly related to mPAP than was RVFAC, 12,13 as also observed in our study. Although we showed that RVFAC was clearly useful, measuring RVEF remains of critical importance in PH, as has been demonstrated by several different groups.…”
Section: Indices Of Rv Function Rv Dilation and Septum Bulgingsupporting
confidence: 80%
See 1 more Smart Citation
“…Míg az MR-rel mért volumenértékek jó korrelációt mutattak a velük identikusnak tekinthető jobb kamrai átmérő és terület értékekkel, addig a jobbkamra-funkció tekintetében az eredményeink kevésbé voltak kedvezőek. Annak ellenére, hogy több publikációban is jó korreláci-ót igazoltak az MR-rel mért jobb kamrai ejekciós frakció és az echokardiográfi ás RVFAC-paraméter között (20,21,22), jelen kutatásunk során nem mutatkozott szignifi káns összefüggés. Ennek oka lehet többek között az, hogy COPD-s, emphysemás mellkasú betegekben a jobb kamra olykor korlátozottan vizualizálható echokardiográfi ával, különösen a csúcsi régióban, így a jobb kamrai terület korrekt körülrajzolása nem mindig lehetséges.…”
Section: Megbeszélésunclassified
“…Due to the strong concealment, acute onset and high mortality rates of cardiovascular disease, early quantitative diagnosis and risk assessment play a crucial role in improvement of human life quality. Anomaly of left ventricular conformation and movement always treated as important basis for cardiovascular disease in clinic recently [1] . However it turns out, the anomaly of right ventricular conformation and functional also have a great value to cardiovascular disease, including and forecasting congenital heart disease(CHD) or acquired heart disease (AHD), such as heart failure, ischemic heart disease, pulmonary hypertension, right ventricular dysplasia induced arrhythmias and dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%